"Ndom heaved": Imagining Igbo women in the Ogu Umunwanyi (1929 Women's War) in Echewa's I Saw the Sky Catch Fire. (June 2020) - Hodapp, James
The power of women to carry out explicit acts of resistance against colonialism has traditionally been of great interest within African literary studies. It is surprising therefore that within the field representations of Ogu Umunwanyi (1929 Women's War) in Nigeria, patronizingly referred to as "riots" in British colonial reports, have received scant attention. This article, in part, compensates for this oversight and asserts the value of one representation of the Ogu Umunwanyi : T. Obinkaram Echewa's 1992 novel I Saw the Sky Catch Fire . This article argues that the novel mobilizes a particularly Igbo women's solidarity, Ndom, to fill out traditional histories and ethnographies of the Ogu . Echewa "Igbofies" the war story at various textual levels to alienate Anglophone readers with seemingly untranslatable words, sayings, and concepts with the ultimate goal of communicating an Igbo women's way of being in the world. Ndom in the novel problematizes conventional Western understandings of time, space, and gender to at once endear non-Igbo readers to a foreign culture while foregrounding the novel's unwillingness to offer the concept as a totalizing project.